2010
DOI: 10.1111/j.1365-3024.2010.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoendocrine host–parasite interactions during helminth infections: from the basic knowledge to its possible therapeutic applications

Abstract: Most of the current research on parasitic infections that affect humans and domestic animals has been focused on vaccines, diagnostic methods, epidemiology, new drug design, and recently, with the advancement of genomics and proteomics, on the evolutionary origins of parasites. However, the basic biology of many parasites of medical and veterinary importance has not been intensively studied. Some efforts have been made to obtain information on the parasite-host relationship; however, knowledge of the intricate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…Recent evidence revealed that estrogens can affect Taenia physiology (13,36). Within this line of evidence, the efficiency of chemoprotective TAM treatment suggests a possible role for the estrogens in Echinococcus development.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence revealed that estrogens can affect Taenia physiology (13,36). Within this line of evidence, the efficiency of chemoprotective TAM treatment suggests a possible role for the estrogens in Echinococcus development.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, hormones can regulate the innate immune response and the subsequent adaptive immune response [180].…”
Section: Resultsmentioning
confidence: 99%
“…Nonimmunological factors like sexual hormones, were proposed to influence the chronicity of the infection (Remoué et al, 2001). Hormones are strongly involved in immune suppression observed in stress-fully conditions which predispose to greater and longer infection or make the host susceptible to infection (Hernandez-Bello et al, 2010). Increases in gastrointestinal nematode egg production in sheep with age were greatest among individuals that had experienced the highest degree of stress (Hayward et al, 2009).…”
Section: When the Immunosuppression Is Usedmentioning
confidence: 99%
“…Neural pathways regulate immune response at regional, local and systemic levels through neurotransmitters and neuropeptides, and may have variable effects on immune cell activation and cytokine production. In turn, cytokines and chemokines produced both at peripheral inflammatory sites and/or locally in the CNS can modulate neural tissue function and hormonal secretion by endocrine glands (Delgado et al, 2004;Escobedo et al, 2005;Hernandez-Bello et al, 2010). One consequence of the invasion of nematode larvae is inflammation and tissue damage which provokes immunosuppression and analgesia.…”
Section: Cytokines and Chemokines Cytokines And Chemokines Il-4↑ Il-13↓mentioning
confidence: 99%